How do you simplify the expression (sec^2theta-1)/sec^2thetasec2θ−1sec2θ? Trigonometry Trigonometric Identities and Equations Fundamental Identities 1 Answer Noah G Oct 30, 2016 =>(1/cos^2theta - 1)/(1/cos^2theta)⇒1cos2θ−11cos2θ => (1/cos^2theta - cos^2theta/cos^2theta)/(1/cos^2theta)⇒1cos2θ−cos2θcos2θ1cos2θ =>((1 - cos^2theta)/cos^2theta)/(1/cos^2theta)⇒1−cos2θcos2θ1cos2θ We use the identity sin^2beta + cos^2beta = 1-> sin^2beta = 1 - cos^2betasin2β+cos2β=1→sin2β=1−cos2β. =>(sin^2theta)/cos^2theta xx cos^2theta/1⇒sin2θcos2θ×cos2θ1 =>sin^2theta⇒sin2θ Hopefully this helps! Answer link Related questions How do you use the fundamental trigonometric identities to determine the simplified form of the... How do you apply the fundamental identities to values of thetaθ and show that they are true? How do you use the fundamental identities to prove other identities? What are even and odd functions? Is sine, cosine, tangent functions odd or even? How do you simplify sec xcos (frac{\pi}{2} - x )secxcos(π2−x)? If csc z = \frac{17}{8}cscz=178 and cos z= - \frac{15}{17}cosz=−1517, then how do you find cot zcotz? How do you simplify \frac{\sin^4 \theta - \cos^4 \theta}{\sin^2 \theta - \cos^2 \theta} sin4θ−cos4θsin2θ−cos2θ using... How do you prove that tangent is an odd function? How do you prove that sec(pi/3)tan(pi/3)=2sqrt(3)sec(π3)tan(π3)=2√3? See all questions in Fundamental Identities Impact of this question 5021 views around the world You can reuse this answer Creative Commons License